Tax Audit and Company Paying its Fair Share of Income Taxes: Evidence from Nigeria - Adekanmi, Aderemi Daniel; Olaniyan, Niyi Oladipo; Efuntade, Alani Olusegun (EuroEconomica, 2022)
The purpose of this study was to investigate the link between tax audits and tax compliance among Nigerian firms. Using a cluster sampling strategy, three hundred (300) questionnaires were sent to companies taxpayers in the South-West zone (comprising the states of Ekiti, Osun, Oyo, and Lagos). A total of one hundred (100) questionnaires were distributed in each state. Ordinary Least Squares was used to examine the hypotheses stated (OLS). Compliance with Nigeria's corporate income tax laws was shown to have a positive relationship with the independent variable (tax audit). Tax audits were shown to have a statistically and positively favorable association with corporate income tax compliance in Nigeria, suggesting that they are helpful in encouraging compliance. According to the findings, the best strategy to promote compliance with corporate income taxes is to use a mix of persuasive (tax justice and tax education) and deterrent (tax audit) tactics.